Poverty among households living in slum area of Hlaing Tharyar Township, Yangon City, Myanmar - Htwe, Thet; Oo, Win M.; Lwin, Nay; Win, Kyaw H.; Dar, Hlaing T. (International Journal of Research in Medical Sciences, 2017)
Background: Slums can be regarded as physical manifestations of urban poverty. Although the world has made dramatic improvement in reducing poverty since 1990, poverty still persists at an unacceptable level. Although current situations highlights the importance of slum areas to be given priority in poverty alleviation, there are limited data on poverty level among people living in urban slums of Myanmar. Methods: A cross-sectional study was conducted among households living in slum areas of Hlaing Tharyar Township, Yangon City, Myanmar during 2016. Multi-staged systematic random sampling and face-to-face interview were applied in selecting the samples and collecting the data, respectively. The new global poverty line (1.9 USD per person per day) was used as a threshold in determining the poverty. Chi-squared test and multivariate logistic regression analysis were utilized in data analysis. Results: Altogether 254 participants were recruited after getting informed consent. The occurrence of poverty among households was 54.3% (95% CI: 48.2%, 60.5%). Head counts of poverty among study population was 58.8%. The education status of household’s head, size of household and the presence of less than 15 years old children in the household were detected as significant determinants of being poor household. Conclusions: Poverty among households living in slum area of Hlaing Tharyar Township, Yangon City was high. Measures to alleviate poverty in urban slums should be intensified. Education level of household’s heads should be improved. Family planning or birth spacing programme should also be strengthened, especially in urban slums.